The Multi-hub Academic Conference: Global, Inclusive, Culturally Diverse, Creative, Sustainable - Parncutt, Richard; Lindborg, PerMagnus; Meyer-Kahlen, Nils; Timmers, Renee (Frontiers in Research Metrics and Analytics, 2021)
New conference formats are emerging in response to COVID-19 and climate change. Virtual conferences are sustainable and inclusive regardless of participant mobility (financial means, caring commitments, disability), but lack face-to-face contact. Hybrid conferences (physical meetings with additional virtual presentations) tend to discriminate against non-fliers and encourage unsustainable flying. Multi-hub conferences mix real and virtual interactions during talks and social breaks and are distributed across nominally equal hubs. We propose a global multi-hub solution in which all hubs interact daily in real time with all other hubs in parallel sessions by internet videoconferencing. Conference sessions are confined to three equally-spaced four-hour UTC timeslots. Local programs comprise morning and afternoon/evening sessions (recordings from night sessions can be watched later). Three reference hubs are located exactly eight hours apart; additional hubs are within two hours and their programs are aligned with the closest reference hub. The conference experience at each hub depends on the number of local participants and the time difference to the nearest reference. Participants are motivated to travel to the nearest hub. Mobility-based discrimination is minimized. Lower costs facilitate diversity, equity, and inclusion. Academic quality, creativity, enjoyment, and low-carbon sustainability are simultaneously promoted.